Novel failure mode of chip corrosion at automotive HALL sensor devices under multiple stress conditions. (September 2016) - Simon-Najasek, M.; Lorenz, G.; Lindner, A.; Altmann, F.
Abstract: Semiconductor devices used in automotive applications undergo numerous stress situations depending on their particular application. Corrosion, as one main crucial failure mechanisms, can affect the lifetime of electronic components on system, device or even die level. In this paper, a novel corrosion mechanism on HALL sensor devices is investigated and clarified. This corrosion is only occurring under complex conditions like layout aspects, ionic impurities combined with humidity penetration and thermo-mechanical strain due to packaging and additional mechanical load from further over moulding. It is shown how advanced physical and chemical analysis can be combined with finite element simulation to ascertain a chemical degradation running on silicon, silicon dioxide and metallisation level to derive the complete chemical reaction mechanism for the observed corrosion defects. To verify the new failure mode, experiments to recreate this type of corrosion were carried out. Finally, conclusions are drawn on how failure modes can be prevented and how the robustness of the HALL devices under harsh environments can be increased.